Cord milking versus immediate clamping in preterm infants: a randomised controlled trial. Issue 2 (19th March 2019) - El-Naggar, Walid; Simpson, David; Hussain, Arif; Armson, Anthony; Dodds, Linda; Warren, Andrew; Whyte, Robin; McMillan, Douglas
Abstract : Objective: To investigate whether umbilical cord milking (UCM) at birth improves systemic blood flow and short-term outcomes, as compared with immediate cord clamping (ICC). Design: Randomised clinical trial. Setting: Single tertiary care centre. Patients: Infants born to eligible women presenting in preterm labour between 24 and 31 weeks' gestation. Interventions: UCM three times at birth or ICC. Outcome measures: Primary outcome included systemic blood flow as represented by echo-derived superior vena cava(SVC) flow at 4–6 hours after birth. The echocardiographer and interpreter were blinded to the randomisation. Secondary outcomes included cardiac output, neonatal morbidities and mortality. Analysis was by intention to treat. Results: A total of 73 infants were randomised (37 to UCM and 36 to ICC). Mean (SD) gestational age was 27 (2) weeks and mean (SD) birth weight was 1040 (283) g. Haemoglobin on admission was higher in the UCM than in the ICC group (16.1 vs 15.0 g/L), p=0.049 (mean difference 1.1, 95% CI 0.003 to 2.2). No statistically significant differences were found between groups in SVC flow at 4–6 hours (88.9±37.8 and 107.3±60.1 mL/kg/min), p=0.13 (mean difference −18.4, 95% CI −41.7 to 5.0 mL/kg/min) or at 10–12 hours of age (102.5±41.8 and 90.6±28.4 mL/kg/min), p=0.17 (mean difference 12.0, 95% CI −4.7 to 28.7 mL/kg/min), cardiac output or neonatal morbidities. Conclusions: Cord milking was not shown to improve functional cardiac outcomes, neonatal morbidity or mortality. More research is needed before routine cord milking can be recommended for very preterm infants. Trial registration: NCT01487187 .